(untitled) (Research, Society and Development, 2022)
Eggshell is a nutrient-rich residue and can be used as a soil amendment and fertilizer. However, it has a slow release, making its use unfeasible, but microorganisms can accelerate the process of nutrient release. Based on this, the objective was to evaluate the solubilization of the eggshell in the culture medium and in the soil by bacterial strains. Two experiments were installed in a completely randomized design, which consisted of 13 treatments, 12 bacterial strains and a control experiment without inoculation. The first experiment was carried out in a 13 x 2 factorial scheme with minimal medium containing eggshell or CaCl2 with four replications. The media were incubated at 28 °C and after three and seven days the growth, the pH of the medium and the concentration of soluble Ca2+ were evaluated by flame atomic emission spectrometry. The second experiment was carried out in plastic flasks in which 175 g of soil and 0.75 g of eggshell were inserted. After incubation, the pH in CaCl2, the potential acidity (H + Al) and the concentration of K+, Ca2+ and Mg2+ were evaluated. In the final analysis, the bacterial strains did not change the pH and Ca2+ values ​​of the culture medium in the in vitro experiment. In the soil experiment, strains 100-40 and 100-5 showed the ability to solubilize eggshell calcium.